A Cross-cultural analysis of communication patterns between two cultures in Southwest Nigeria (2017)
Communication scholars estimate that two-thirds of communications are influenced by the culture of the communicator. On this basis, this study examined the Igbo and Yoruba socio-cultural relationships as they influence the management of their communication patterns. Employing the mixed-method research design, the study revealed the cultural affinity in both ethnic groups’ communication patterns in the use of honorific greeting, silence, expressiveness (direct or indirectness and touch) and eye contact. This shows that culture has a significant influence on some of the communication patterns of both ethnic groups (p>0.000) while gender also has an influence on both groups (r=20.7, df=l, p<.05). This shows a slight variation in both ethnic groups in relation to their culturally held values. The findings of this study will play a significant role in the promotion of effective communication and peaceful coexistence among cultural groups.